Eksplorasi Cerita Rajapala Sebagai Inspirasi Dalam Penciptaan Seni Lukis Komik Digital - Aryandika, Made; Gulendra, I Wayan; Mudana, I Wayan (Program Studi Seni Murni ISI Bali, 2022)
Rajapala's story is a symbol of the love and escaptic marriage between man and angel. The message that can be gleaned from this story or literary work is